Enhanced VEGF-A expression and mediated angiogenic differentiation in human gingival fibroblasts by stimulating with TNF-α in vitro - Yanli Wang; Congchong Yang (Elsevier, 2022)
Backgroud/purpose: The effects of inflammatory cytokines were reported to involve in the process of periodontal disease and inflamed tissue enhanced the expression of inflammatory mediators which in turn may promote angiogenesis. Human gingival fibroblasts (HGFs) exert the basic function in periodontal tissue repair and regeneration. However, studies specially focused on the effects of inflammation-related HGFs on angiogenic and osteogenic differentiation are limited. This study was aimed to test whether HGFs enhance vascular endothelial growth factor (VEGF)-A expression mediating angiogenic and osteogenic differentiation by stimulating with tumor necrosis factor-α (TNF-α), to further identify the possible mechanism which may be responsible for this activity. Materials and methods: In this study, HGFs are treated by TNF-α in order to detect the effects of angiogenic and osteogenic differentiation under inflammation-related condition. Results: TNF-α enhances VEGF-A expression and results in increasing cell migration and angiogenic differentiation and inhibiting osteogenic differentiation in HGFs. Besides, TNF-α stimulated VEGF-A-mediated angiogenic differentiation is dependent on the activation of mitogen-activated protein kinase (MAPK) pathway, Extracellular signal-regulated kinase (ERK) 1/2 phosphorylation may contribute to regulate the function of VEGF-A in inflammation-related HGFs. Conclusion: This study demonstrated that enhanced VEGF-A-mediated angiogenic differentiation in HGFs is dependent on the activation of MAPK pathway by stimulating with TNF-α in vitro. Therefore, this study could provide better understand for the progression of inflammation-related periodontal diseases.